THE INFLUENCE OF TEACHER S TEACHING STYLE AND LEARNING DISCIPLINE ON STUDENTS COGNITIVE ABILITY AT SMP NEGERI 3 MOTOLING TIMUR - Herman Dolonseda; Joubert M. Dame; Agsel Lendongan (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2023)
This study aims to determine the effect of the teacher s teaching style and learning discipline on the cognitive abilities of students at SMP Negeri 3 Motoling Timur This test strategy is a learning technique with an example of 75 individuals The procedure used in collecting information is a survey strategy poll and documentation The results of the examination were dissected using various recurrence direct examinations basic connection examinations and various connection examinations The results showed: 1 There is an influence between the Teacher s Teaching Style on the Cognitive Ability of students of SMP Negeri 3 Motoling Timur by 44 89 with t count gt; t table = 7 71 gt; 2 04 and F count gt; F table < p> Keywords: Teacher s Teaching Style Learning Discipline Students Cognitive Ability< strong>< p>